PENGARUH KEPEMIMPINAN, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH KABUPATEN KERINCI: ETRA, S.KOM - ETRA (JURNAL ADMINISTRASI NUSANTARA, 2021)
Human resources (HR) is one of the most important factors that cannot even be separated from an organization, both institutions and companies. The government in carrying out its duties and responsibilities are required to produce good performance. This study aims to determine the effect of leadership, competence and work discipline on employee performance. The sample used in this study as many as 9 5 respondents who are at BKPSDMD Kerinci. The analytical method used in this study is multiple linear regression analysis. The results of this study indicate that leadership influences and significantly affects employee performance , competence influences and significantly affects employee performance, work discipline has a significant effect on employee performance, leadership , competence and work discipline jointly influences and significantly affects the performance of Kerinci Regency BKPSDMD employees.